The Efficacy of Biofeedback Therapy for the Treatment of Fecal Incontinence After Soave Procedure in Children for Hirschsprung's Disease - Yuan, Yuhang; Xu, Mengyao; Yang, Heying; Sun, Beibei; Li, Yanan; Zhang, Ning; Wang, Guantao; Su, Fan (Frontiers in Pediatrics, 2021)
Introduction: Hirschsprung's disease is a common digestive tract malformation in children, and the Soave procedure is one of the classic surgical methods for Hirschsprung's disease (HD). Fecal incontinence is one of the most common postoperative complications that can cause significant distress to the patients and their family, the incidence of which is 20% in a recent series. Biofeedback therapy (BFT) can be an effective treatment for managing anorectal disorders, but there has been little report of the efficacy of BFT for the treatment of fecal incontinence after the Soave procedure, and the main objective of this study is to evaluate it. Methods: We retrospectively analyzed postoperative fecal incontinence in 46 children who received the Soave procedure for HD and who received BFT at our institution from March 2016 to February 2020, which included 38 males and 8 females (mean age 8.1 years, from 3.7 to 14 years). Anal sphincter contraction training was performed using BFT for 10 days per session in the hospital, one time each day, and 20 min each time. BFT was performed by employing visual and verbal feedback techniques using the biofeedback instrument. Long-term functional outcomes were objectively assessed using the Rintala Bowel Function Score (RBFS), and the patients were scored according to the sum total as excellent (18–20 points, 0 case), good (11–16 points, 0 case), fair (9–11 points, 9 cases), or poor (6–9 points, 37 cases). Defecation questionnaires and anorectal manometry were completed pretreatment and after three, six, or nine sessions, and primary outcome measures of anorectal manometry were anal maximal contraction pressure (AMCP), anal longest contraction time (ALCT), rectal rest pressure (RRP), and anal rest pressure (ARP). Results: Followed up from 6 months to 4 years, the symptoms of fecal incontinence disappeared completely in 39 (84.78%) patients. Among them, 14 (30.43%) had complete disappearance of symptoms after 3 sessions of treatment, 25 (54.34%) patients had improved symptoms after 6 sessions of treatment, symptoms completely disappeared after 6 sessions of treatment, and 7 (15.22%) cases still suffered fecal incontinence mildly. The AMCP after three and six sessions in the poor group was significantly increased compared with that before treatment [(85.87 ± 31.75) mmHg vs. (135.33 ± 37.69) mmHg vs. (128.41 ± 33.45) mmHg, P < 0.05]. The ALCT and ARP showed the same trend, while the RRP after three and six sessions were not significant (P > 0.05). The mean (±SD) score of the RBFS increased from 9 to 17.40 ± 0.84 in the fair group, while it increased from 7.22 ± 0.76 to 16.58 ± 1.66 in the poor group after six sessions (P < 0.05). Conclusion: Biofeedback therapy is a safe and effective treatment of fecal incontinence after the Soave procedure of children for Hirschsprung's disease. It is beneficial to design the individualized treatment programs for the children with varying degrees of fecal incontinence.